A novel method for digital data encoding-decoding - Amjad Y. Hindi (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2020)
Cryptography is one of the paramount and most vital data treatment processes, it allows us to be secure in our electronic transactions. The process of cryptography protects our valuable data such as private account numbers and transaction amounts, electronic signatures replace handwritten signatures or credit card authorizations, and public-key encryption provides confidentiality. The objective of data encryption is to keep digital data confidentiality save as it is stored on computer systems and transferred using the internet or other computer networks. In this paper we will focus in enhancing security level of the encryption-decryption process by introducing a novel method, which uses any digital color image to encode-decode secret message, the using of a special key to encrypt-decrypt the encoded-decoded message, the color image will be known only by the transmitter and receiver to keep the process of data treatment confidential, the obtained experimental results by the proposed method will be analyzed to prove the enhancement in process efficiency and confidentiality.